Learning From Exemplary Teachers of Literacy. (28th December 2017) - Duke, Nell K.; Cervetti, Gina N.; Wise, Crystal N.
Abstract: Recent articles in The Reading Teacher have communicated contributions of reading research over the last three decades. In this article, the authors focus on a type of research that has contributed to our understanding of practice: studies of exemplary teachers of literacy. The authors discuss three studies and their findings: a study of a teacher who was exemplary in fostering the literacy achievement of African American students; a study of two teachers who were, in comparison with five other teachers studied, exemplary in fostering literacy engagement; and a study of 36 teachers who were more and less effective at fostering literacy growth. These and other studies of exemplary teachers reveal a wide range of instructional practices and their orchestration.